Coproduciendo Categorías étnico-raciales: empadronadores en el Censo Nacional de Perú 2017 - Gonzales Huaman, Meylin (2021)
Scholarly work that examines the production of ethnoracial categories has more closely examined the role of nation-states, social movements, and transnational trends. This focus has shifted attention away from the internal institutional processes that influence the production of ethnoracial categories. In particular, the role of the census-takers as key actors in these institutional processes has been underexamined. In this study, we draw from fifty-four semi-structured interviews with census-takers who participated in the 2017 Peruvian National Census to argue that census-takers can be considered street-level bureaucrats because of the influence they exercise in the production of ethnoracial categories. In a context where ethnoracial categories are contested, participants in our study drew from their own understandings of the ethnoracial question which ultimately –albeit inadvertently– influenced the self-identification of household members and, to a greater extent, increased the probability that household members self-identify as mestizo. Although census-takers play a temporary role, they are still important actors who can be considered street-level bureaucrats in the production of ethnoracial categories in contexts where these categories are continuous subjects of debate and contestation.